Meta-Analysis of The Effect of ICT-Based Learning Media on Students' Biology Learning Outcomes - Kurnia Ningsih; Anisyah Yuniarti; Afandi Afandi; Ahmad Yani T (JETL (Journal of Education, Teaching and Learning), 2023)
The use of ICT-based learning media can improve student learning outcomes. Re-analysis was carried out in this study regarding the use of ICT-based learning media in improving student learning outcomes from the theses that had been selected and selected in line with the topics studied. This study aims to determine the meta-analysis of the effect of using ICT-based learning media on students' biology learning outcomes. This type of research is descriptive survey research. Using a purposive sampling technique, 20 theses of Biology education students at FKIP Untan for the 2017-2021 period were summarized. The calculation of the effect size of 20 undergraduate thesis students in biology education resulted in an average effect size of 0.85 (SD = 2.80). It shows that ICT-based learning media contributed 32.89% to improving student biology learning outcomes. The ICT-based learning media type with the most significant influence is video media, with an average effect size of 1.18 (SD = 4.34). Video media contributed 37.08% to increasing student biology learning outcomes. The relationship between variables obtained from research results based on the material taught and the use of ICT-based learning media that has the most significant influence is applied to the digestive system material with an average effect size of 1.18 (SD = 4.34). ICT-based learning media can improve students' biology learning outcomes in digestive system material by 37.08%. Based on the school level, ICT-based learning media that significantly influences students' biology learning outcomes is implemented in junior high schools. Using ICT-based learning media can improve student biology learning outcomes in junior high schools by 42%.